日本と韓国の小・中学校英語教育の比較検討: 英語教材の分析を足がかりとして - 中村, 洋 (北海道英語教育学会 紀要, 2010)
Foreign Language Activities will begin for 5th and 6th grade students in elementary schools in Japan by 2011. The Ministry of Education, Culture, Sports, Science and Technology produced Eigo Note as supplementary material to assist these activities. The aim of this paper is to consider the practicality of not only Eigo Note, but also the elementary and junior high school (J.H.S.) English textbooks of Japan and Korea as well. Eigo note has included vocabulary that has been selected carefully and used repeatedly, however, its activities are predominately speaking based. When compared with the elementary school textbooks of Korea, an insufficient number of writing tasks appear in it. The target sentences in book 1 of the J.H.S. textbook in Japan are inappropriate for the age of the students. In future revisions of Eigo Note and J.H.S. textbooks, there might be a need to adapt the level of difficulty of activities, especially the writing tasks in Eigo Note must be reconsidered. Results also indicate that the English education system and textbooks in Korea were well designed to link the activities in elementary schools with J.H.S. English education, whereas Japanese ones are insufficient in terms of cooperation across the elementary and J.H.S. curriculum.